The changing seasonality of mixed layer temperature in the Arctic shelf seas in response to surface heat flux forcing - Chuanshuai Fu; Wenli Zhong; Clark Pennelly; Paul G. Myers (Ocean Modelling, 2026)

Recent intensification of the negative physiological effect of CO2 on terrestrial evaporation - Haiyang Qian; Weiguang Wang; Zefeng Chen; Akash Koppa; Guoshuai Liu; Jian Zeng; Jianyu Fu; Shuai Cheng; Diego G. Miralles (Journal of Hydrology, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Hierarchical regulation and molecular functions of co-transcriptional splicing - Rui Niu; Aiming Zhang; Michael G. Rosenfeld; Xiang-Dong Fu; Yajing Hao (Science Bulletin, 2026)

Two new species of the eel genus Facciolella from Taiwan , northwestern Pacific Ocean ( Anguilliformes: Nettastomatidae ) - Hsuan‐Ching Ho; Jian‐Fu Huang; David G. Smith (Journal of Fish Biology, 2026)
Two new species of the duckbill eel genus Facciolella are described based on specimens collected off Taiwan, representing the first record of the genus in the western Pacific Ocean. Facciolella bicolor sp. nov ., based on three types, is most similar to F. smithi in having a bicoloured body and trunk, and can be distinguished by more preanal lateral‐line pores and preanal vertebrae and a combination of characters. Facciolella punctatus sp. nov ., based on six type specimens, is distinct in having a pale body and scattered black dots, and a combination of characters. The DNA barcoding analysis also supports the establishment of both new species. Detailed descriptions and figures are provided. The leptocephali found in the Pacific Ocean are also discussed.

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Thallium isotope insights into Mn Oxides as precursor to Ediacaran Mn Carbonate Ore - Xuwen Luo; Haifeng Fan; Jean Clemente; Chao Li; Hongjie Zhang; Long Chen; Yaowen Wu; Shaohong Fu; Jianfeng Gao; Hanjie Wen; Sune G. Nielsen (Geochimica et Cosmochimica Acta, 2026)

Contrasting behaviour in geogenic degassing along an active segment of the East Anatolian fault zone (Türkiye) - G. Yüce; W. D'Alessandro; C.C. Fu; F. Italiano; M. İçhedef; H. Elmacı; B. Kürkcüoğlu; B. Kahraman; A. Demirtaş; L.H. Lin; D. Yasin; Ş. Gürboğa; et al. (Applied Geochemistry, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Fixation of atmospheric nitrogen on present-day Mars during dust events - Wenshuo Mao; Xiaohui Fu; Zhongchen Wu; Jiang Zhang; Zongcheng Ling; Yang Liu; Yu-Yan Sara Zhao; Jiacheng Liu; He Cui; Hitesh G. Changela; Yuheng Ni; Lifang Li; et al. (Earth and Planetary Science Letters, 2026)

Discovery, herbicidal activity evaluation, and mechanism of action of Heteroaryl chalcones as novel HPPD inhibitors - Li-xia Zhao; Dmitry B. Rubinov; Pan-xiu Zhang; Veronica G. Zinovich; Wen-qing Yu; Tatyana S. Khlebnicova; Fei Ye; Ying Fu; Fedor A. Lakhvich (Pesticide Biochemistry and Physiology, 2026)

Raman mapping reveals alpha radiation damage zonation and its annealing in Durango apatite - Xiaowei Zeng; Guido Pastore; Chuanbo Shen; Alberto Resentini; Hongyang Fu; Chaoqun Yang; Yannick Buret; Pieter Vermeesch; Marco G. Malusà (Earth and Planetary Science Letters, 2025)

Prof Stephen P. Long, FRS (1950–2025) - Lorenzo Álvarez‐Filip; Edith Bai; Carl J. Bernacchi; Rhea Bruno; Klaus Butterbach‐Bahl; Maria Byrne; I‐Ching Chen; Shaolin Chen; William W. L. Cheung; M. Francesca Cotrufo; Tatenda Dalu; Xiaojuan Feng; et al. (Global Change Biology, 2025)

Metallogenic age and geological significance of the Jiazishan Mo deposit, Inner Mongolia, China - Z. L. Wang; J. Z. Yang; K. Q. Zhao; Y. G. Fu; J. W. Gao; Y. M. Deng; L. J. Lin; Z. Duan (Australian Journal of Earth Sciences, 2025)

Effects of agricultural inputs on soil virome-associated antibiotic resistance and virulence: A focus on manure, microplastic and pesticide - Wen-Jing Li; Timothy M. Ghaly; Sasha G. Tetu; Fu-Yi Huang; Hong-Zhe Li; Hua Li (Journal of Hazardous Materials, 2025)

A low oxygen threshold for physiological responses and trace metal quotas of Prochlorococcus and Synechococcus - Joan De Vera; Yuanyuan Feng; Feixue Fu; Shun‐Chung Yang; Amjad Mansour; Nicholas J. Hawco; David A. Hutchins; Seth G. John (Limnology and Oceanography, 2025)
Continued human activity is expected to accelerate ocean deoxygenation, leading to the expansion and shallowing of oxygen‐deficient zones (ODZs). This decline in oxygen may impact both phytoplankton growth and trace metal uptake. We conducted culture experiments with Prochlorococcus MIT9313 and Synechococcus XM‐24, two numerically dominant genera of marine picocyanobacteria, under varying O 2 levels (36–242 μ M). These experiments provide some of the first data on trace metal quotas in phytoplankton under varying O 2 conditions in culture. Moderate deoxygenation, above hypoxic levels, did not negatively impact the growth and trace metal quotas of either Prochlorococcus MIT9313 or Synechococcus XM‐24 (80 and 85 μ M O 2 , respectively). Indeed, some parameters (e.g., growth rate, carbon fixation and chlorophyll fluorescence) suggest slight growth enhancement at these moderate levels of deoxygenation. However, hypoxic conditions (36 μ M O 2 ) significantly inhibited the growth of Prochlorococcus MIT9313, suggesting a minimum O 2 threshold needed to prevent disruptions in O 2 ‐dependent processes. Synechococcus XM‐24 exhibited no significant response to elevated p CO₂ (1054 μ atm), indicating possible adaptation to variable coastal CO₂ environments. Changes in trace‐metal quotas (metal‐to‐phosphorous ratios; metal/P) were also observed when Prochlorococcus MIT9313 was cultured under hypoxia, including up to 48% increases in Fe/P, 48% decreases in Ni/P, and 27% decreases in Co/P, compared to oxic conditions. These results contrast with elevated metal/P ratios in autotrophic‐associated particles from ODZs, suggesting either distinct metal uptake strategies by phytoplankton in low‐O 2 regions or that elevated particulate metals are influenced by other plankton types such as heterotrophs.

Physical rather than chemical protection determines soil organic carbon accumulation in a subtropical Chinese fir plantation treated by litter manipulation - Qiao Liu; Xiangjiang Liu; Zhigao Liao; Shengnan Wang; Junjie Huang; Yiqi Luo; Lifen Jiang; Geoff G. Wang; Huiming Wang; Fu-Sheng Chen (Plant and Soil, 2025)

The molecular weight-dependent redox capacity of soil dissolved organic matter: Roles of aromaticity and organic sulfur - Jiang Xiao; Zhenqing Shi; Fu Liu; Qianting Ye; Lanlan Zhu; Quan Gao; Xin Yang; Paul G. Tratnyek (Geochimica et Cosmochimica Acta, 2025)

Phosphorus recovery through struvite crystallization from real wastewater: Bridging gaps from lab to market - Yixin Yan; Nomiki I. Kallikazarou; Olympia Nisiforou; Qingyu Shang; Dafang Fu; Maria G. Antoniou; Ioannis A. Fotidis (Bioresource Technology, 2025)

Removal of fluoroquinolone antibiotic from wastewater based on immobilized metal affinity mechanism - L Zhao; B. Jia; M. He; H. Hu; Y. Guo; G. Fu; C. Hou; S. Gao; R. Li; X. Lv (International Journal of Environmental Science and Technology, 2025)

Gold nanoparticles mediate suppression of angiogenesis and breast cancer growth via MMP-9/NF-κB/mTOR and PD-L1/PD-1 signaling: integrative in vitro validation and network pharmacology insights - Alaa Elmetwalli; Tarek El-Sewedy; Mervat G. Hassan; Mohamed O. Abdel-Monem; Jihan Hassan; Nadia F. Ismail; Afrah Fatthi Salama; Junjiang Fu; Nasser Mousa; Deema Kamal Sabir; Ola El-Emam; Ghada Hamdy; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Wind Direction and Strength Determine the Genetic Structure of an Insect‐Pollinated Plant Across Heterogeneous Landscape - Jun‐Yin Deng; Rong‐Hua Fu; Stephen G. Compton; Chuan Yuan; Matthew M. Kling; Xiao‐Yong Chen; Yao‐Bin Song; Kai Jiang; Mei Liu; Jaco M. Greeff; Yan Chen (Journal of Biogeography, 2025)
Aim Dispersal of plant propagules and their genes is crucial for plant responses to landscape heterogeneities, yet the mechanisms behind this dispersal remain unclear. Ficus species depend on wind‐borne fig wasps for pollination, but research on airflow effects on Ficus genetic structure has produced conflicting results. Our study aims to clarify the role of wind in shaping the genetic structure of such plants with wind‐borne insect pollinators by examining how geomorphological complexity interacts with air movements to influence genetic structures. Location Southwest China: Sichuan, Yunnan, Guangxi and Guizhou provinces. Taxon Ficus tikoua Bur., Ficus , Moraceae. Methods We sampled 56 F. tikoua sites across southwest China, characterised by high geomorphologic complexity. River basins and predominant winds were visualised across the sampled regions. Wind connectivity between sampled sites during the main pollination season was modelled based on hourly daily wind data. The maternal and biparental genetic structure of sites were reconstructed using chloroplast DNA (cpDNA) and nuclear SSR (nuSSR) markers. Links between genetic structure, location, and wind parameters were estimated by Mantel or partial Mantel tests. Results The plant's maternal genetic structure was defined by river systems, with two distinct cpDNA groups located in the Yangtze and Pearl River basins, respectively. The boundaries for nuclear variation were less clearly delimited geographically. Sites with mixtures of nuSSR groups were concentrated where prevailing winds arrived from several directions. Stronger between‐site air flows increased nuSSR geneflow and genetic similarities, while populations receiving more wind flow were also more genetically variable. Main Conclusions Our study reveals how plant gene dispersal reflects air and water movements that in turn respond to geomorphologic complexity, thereby directly demonstrating the effects of wind on gene flow of plants with wind‐borne insect pollinators. Wind data matching pollinator flight times and large sample sizes are crucial for testing wind effects.

Spatial Pattern of Active Pollination in Ficus: Younger Floral Adapting to Relatively Dry and Warm Condition - Chuan Yuan; Ronghua Fu; Xuemao Zhang; Stephen G. Compton; Lu Tan; Bin Ai; Yan Chen (Journal of Biogeography, 2025)
Aims Pollination plays a fundamental role in structuring the reproductive strategies and related traits of host plants. Active pollination is only observed in nursery mutualistic systems. However, the mechanisms underlying their maintenance are unclear. We aimed to explore the underlying factors shaping its global distribution pattern in Ficus species specifically putting forward three questions: (1) are actively‐pollinated Ficus species more concentrated in areas with older Ficus floras? (2) Is active pollination better represented in areas with higher and more stable, less seasonal temperatures? (3) And is active pollination also more strongly represented in arid areas? Location Global. Time Period Current. Major Taxa Studied Ficus and pollinating fig wasps. Methods Using the data of 240 species, we constructed global distribution maps of actively‐ and passively‐pollinated Ficus species and estimated their proportions in 80 × 80 km grid cells. We assessed the relative contribution of climate conditions, sexual systems and phylogenetic ages to the geographic variation in frequencies of active pollination using spatial autocorrelation analysis, a spatial linear model and structural equation models. Results Neither active nor passive pollination is randomly distributed. Actively‐pollinated Ficus are more prevalent in regions with a higher proportion of recently divergent Ficus floral elements. Actively‐pollinated species are also more concentrated at lower latitudes with higher and more stable temperatures, and in arid areas. Main Conclusions Our study provides a comprehensive overview of the geographical distribution of pollination modes and sexual systems in Ficus species. Both evolutionary history and current climate are related to the geographic distributions of pollination modes. Active pollination is more prevalent in lineages that diverged recently in the evolutionary history of Ficus and is more associated with relatively dry and warm climates.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Alleviating Nitrogen and Phosphorus Limitation Does Not Amplify Potassium‐Induced Increase in Terrestrial Biomass - Guopeng Liang; Pengyan Sun; Bonnie G. Waring; Zheng Fu; Peter B. Reich (Global Change Biology, 2025)
Potassium (K) is the second most abundant nutrient element in plants after nitrogen (N), and has been shown to limit aboveground production in some contexts. However, the role of N and phosphorus (P) availability in mediating K limitation in terrestrial production remains poorly understood; and it is unknown whether K also limits belowground carbon (C) stocks, which contain at least three times more C than those aboveground stocks. By synthesizing 779 global paired observations (528, 125, and 126 for aboveground productivity, root biomass, and soil organic C [SOC], respectively), we found that K addition significantly increased aboveground production and SOC by 8% and 5%, respectively, but did not significantly affect root biomass (+9%). Moreover, enhanced N and/or P availability (through N and P addition) did not further amplify the positive effect of K on aboveground productivity. In other words, K had a positive effect on aboveground productivity only when N and/or P were limiting, indicating that K could somehow substitute for N or P when they were limiting. Climate variables mostly explained the variations in K effects; specifically, stronger positive responses of aboveground productivity and SOC to K were found in regions with high mean annual temperature and wetness. Our results suggest that K addition enhances C sequestration by increasing both aboveground productivity and SOC, contributing to climate mitigation, but the positive effects of K on terrestrial C stocks are not further amplified when N and P limitations are alleviated.

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Acceptability of a Fresh Produce Intervention for Individuals With Serious Mental Illnesses - Gabriella Farland; Leah G. Pope; En Fu; Dana Cohen; Cheryl Gerstler; Merrill Rotter; Michael T. Compton (Journal of Nutrition Education and Behavior, 2025)

Contrasting molecular structures and photooxidation behaviors between dissolved organic sulfur released from rice straw-biochar and aerobically decomposed rice straw - Chenhui Wei; Heyun Fu; Xiaolei Qu; Shu Tao; Patrick G. Hatcher; Dongqiang Zhu (Chemical Geology, 2025)

Perspective of explosive cyclones with three shapes of upper-level potential vorticity over the northern Atlantic Ocean - J. Ni; G. Fu; L. J. Chen; P. Y. Li (Climate Dynamics, 2025)

Bio-inspired sustainable electrospun quantum nanostructures for high quality factor enabled face masks and self-powered intelligent theranostics - Loganathan Veeramuthu; Ren-Jie Weng; Wei-Hung Chiang; Archana Pandiyan; Fu-Jie Liu; Fang-Cheng Liang; G. Ranjith Kumar; Hua-Yi Hsu; Yu-Ci Chen; Wen-Yinn Lin; Yao-Chun Tang; Wan-Rong Lin; et al. (Chemical Engineering Journal, 2024)

Maternal arsenic exposure modifies associations between arsenic, folate and arsenic metabolism gene variants, and spina bifida risk: A case‒control study in Bangladesh - Chih-Fu Wei; Gwen Tindula; Sudipta Kumer Mukherjee; Xingyan Wang; Sheikh Muhammad Ekramullah; D.M. Arman; Md Joynul Islam; Mubinul Azim; Asifur Rahman; Shamantha Afreen; Md Ziaddin; Benjamin C. Warf; et al. (Environmental Research, 2024)

Computer-aided design and optimization of a multi-level fruit catching system for fresh-market fruit harvesting - Kaiming Fu; Stavros G. Vougioukas; Brian N. Bailey (Computers and Electronics in Agriculture, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Klotho enhances diastolic function in aged hearts through Sirt1-mediated pathways - Nastaran Daneshgar; Renny Lan; Michael Regnier; Samuel G. Mackintosh; Ravinandan Venkatasubramanian; Dao-Fu Dai (GeroScience, 2024)

Reproducible responses of geochemical and microbial successional patterns in the subsurface to carbon source amendment - Jonathan P. Michael; Andrew D. Putt; Yunfeng Yang; Benjamin G. Adams; Kathryn R. McBride; Yupeng Fan; Kenneth A. Lowe; Daliang Ning; Sindhu Jagadamma; Ji Won Moon; Dawn M. Klingeman; Ping Zhang; et al. (Water Research, 2024)

Sensitivity and consistency of long- and short-read metagenomics and epicPCR for the detection of antibiotic resistance genes and their bacterial hosts in wastewater - Esther G. Lou; Yilei Fu; Qi Wang; Todd J. Treangen; Lauren B. Stadler (Journal of Hazardous Materials, 2024)

Evaluation of weak genotoxicity of hydroxychloroquine in human TK6 cells - Xilin Li; Yuan Le; Yuxi Li; Si Chen; Lei Guo; Xin Fu; Mugimane G. Manjanatha; Nan Mei (Toxicology Letters, 2024)

Exceptional sea ice loss leading to anomalously deep winter convection north of Svalbard in 2018 - Chuanshuai Fu; Paul G. Myers (Climate Dynamics, 2024)
An important question is will deep convection sites, where deep waters are ventilated and air-gas exchange into the deep ocean occurs, emerge in the Arctic Ocean with the warming climate. As sea ice retreats northward and as Arctic sea ice becomes younger and thinner, air-sea interactions are strengthening in the high-latitude oceans. This includes new and extreme deep convection events. We investigate the associated physical processes and examine impacts and implications. Focusing on a region near the Arctic gateway of Fram Strait, our study confirms a significant sea ice cover reduction north of Svalbard in 2018 compared to the past decade, shown in observations and several numerical studies. We conduct our study using the regional configuration Arctic and North Hemisphere Atlantic of the ocean/sea ice model NEMO, running at 1/12° resolution (ANHA12). Our numerical study shows that the open water condition during the winter of 2018 allows intense winter convection over the Yermak Plateau, as more oceanic heat is lost to the atmosphere without the insulating sea ice cover, causing the mixed layer depth to reach over 600 m. Anomalous wind prior to the deep convection event forces offshore sea ice movement and contributes to the reduced sea ice cover. The sea ice loss is also attributed to the excess heat brought by the Atlantic Water, which reaches its maximum in the preceding winter in Fram Strait. The deep convection event coincides with enhanced mesoscale eddy activity on the boundary of the Yermak Plateau, especially to the east. The resulting substantial heat loss to the atmosphere also leads to a heat content reduction integrated over the Yermak Plateau region. This event can be linked to the minimum southward sea ice volume flux through Fram Strait in 2018, which is a potential negative freshwater anomaly in the subpolar Atlantic.

A new discovery of 423.6 Ma Hongbaoshan gabbro in the Beishan area, NW China, and its geological significance - Y. G. Fu (Australian Journal of Earth Sciences, 2024)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

Constitutively Synergistic Multiagent Drug Formulations Targeting MERTK, FLT3, and BCL-2 for Treatment of AML - James M. Kelvin; Juhi Jain; Aashis Thapa; Min Qui; Lacey A. Birnbaum; Samuel G. Moore; Henry Zecca; Ryan J. Summers; Jeffrey M. Switchenko; Emma Costanza; Biaggio Uricoli; Xiaodong Wang; et al. (Pharmaceutical Research, 2023)

Large‐scale exploration of nitrogen utilization efficiency in Asia region for rice crop: Variation patterns and determinants - Yuming Sun; Limin Gao; Xusheng Meng; Jian Huang; Junjie Guo; Xuan Zhou; Guohai Fu; Yang Xu; Leslie G. Firbank; Min Wang; Ning Ling; Xumeng Feng; et al. (Global Change Biology, 2023)
Improving rice nitrogen utilization efficiency (NUtE) is imperative to maximizing future food productivity while minimizing environmental threats, yet knowledge of its variation and the underlying regulatory factors is still lacking. Here, we integrated a dataset with 21,571 data compiled by available data from peer‐reviewed literature and a large‐scale field survey to address this knowledge gap. The overall results revealed great variations in rice NUtE, which were mainly associated with human activities, climate conditions, and rice variety. Specifically, N supply rate, temperature, and precipitation were the foremost determinants of rice NUtE, and NUtE responses to climatic change differed among rice varieties. Further prediction highlighted the improved rice NUtE with the increasing latitude or longitude. The indica and hybrid rice exhibited higher NUtE in low latitude regions compared to japonica and inbred rice, respectively. Collectively, our results evaluated the primary drivers of rice NUtE variations and predicted the geographic responses of NUtE in different varieties. Linking the global variations in rice NUtE with environmental factors and geographic adaptability provides valuable agronomic and ecological insights into the regulation of rice NUtE.

RNA sequencing in Artemisia annua L explored the genetic and metabolic responses to hardly soluble aluminum phosphate treatment - Lingyun Wan; Qiulan Huang; Xiaowen Ji; Lisha Song; Zhanjiang Zhang; Limei Pan; Jine Fu; Rania G. Elbaiomy; Ahmed S. Eldomiaty; Shabir A. Rather; Mohamed M. A. Elashtokhy; Jihai Gao; et al. (Functional & Integrative Genomics, 2023)

Ecophysiological and genomic analyses of a representative isolate of highly abundant Bacillus cereus strains in contaminated subsurface sediments - Jennifer L. Goff; Elizabeth G. Szink; Michael P. Thorgersen; Andrew D. Putt; Yupeng Fan; Lauren M. Lui; Torben N. Nielsen; Kristopher A. Hunt; Jonathan P. Michael; Yajiao Wang; Daliang Ning; Ying Fu; et al. (Environmental Microbiology, 2022)
Bacillus cereus strain CPT56D‐587‐MTF (CPTF) was isolated from the highly contaminated Oak Ridge Reservation (ORR) subsurface. This site is contaminated with high levels of nitric acid and multiple heavy metals. Amplicon sequencing of the 16S rRNA genes (V4 region) in sediment from this area revealed an amplicon sequence variant (ASV) with 100% identity to the CPTF 16S rRNA sequence. Notably, this CPTF‐matching ASV had the highest relative abundance in this community survey, with a median relative abundance of 3.77% and comprised 20%–40% of reads in some samples. Pangenomic analysis revealed that strain CPTF has expanded genomic content compared to other B. cereus species—largely due to plasmid acquisition and expansion of transposable elements. This suggests that these features are important for rapid adaptation to native environmental stressors. We connected genotype to phenotype in the context of the unique geochemistry of the site. These analyses revealed that certain genes (e.g. nitrate reductase, heavy metal efflux pumps) that allow this strain to successfully occupy the geochemically heterogenous microniches of its native site are characteristic of the B. cereus species while others such as acid tolerance are mobile genetic element associated and are generally unique to strain CPTF.

Temperature variability interacts with mean temperature to influence the predictability of microbial phenotypes - Fei‐Xue Fu; Bernhard Tschitschko; David A. Hutchins; Michaela E. Larsson; Kirralee G. Baker; Allison McInnes; Tim Kahlke; Arjun Verma; Shauna A. Murray; Martina A. Doblin (Global Change Biology, 2022)
Despite their relatively high thermal optima ( T opt ), tropical taxa may be particularly vulnerable to a rising baseline and increased temperature variation because they live in relatively stable temperatures closer to their T opt . We examined how microbial eukaryotes with differing thermal histories responded to temperature fluctuations of different amplitudes (0 control, ±2, ±4°C) around mean temperatures below or above their T opt . Cosmopolitan dinoflagellates were selected based on their distinct thermal traits and included two species of the same genus (tropical and temperate Coolia spp.), and two strains of the same species maintained at different temperatures for >500 generations (tropical Amphidinium massartii control temperature and high temperature, CT and HT, respectively). There was a universal decline in population growth rate under temperature fluctuations, but strains with narrower thermal niche breadth (temperate Coolia and HT) showed ~10% greater reduction in growth. At suboptimal mean temperatures, cells in the cool phase of the fluctuation stopped dividing, fixed less carbon (C) and had enlarged cell volumes that scaled positively with elemental C, N, and P and C:Chlorophyll‐ a . However, at a supra‐optimal mean temperature, fixed C was directed away from cell division and novel trait combinations developed, leading to greater phenotypic diversity. At the molecular level, heat‐shock proteins, and chaperones, in addition to transcripts involving genome rearrangements, were upregulated in CT and HT during the warm phase of the supra‐optimal fluctuation (30 ± 4°C), a stress response indicating protection. In contrast, the tropical Coolia species upregulated major energy pathways in the warm phase of its supra‐optimal fluctuation (25 ± 4°C), indicating a broadscale shift in metabolism. Our results demonstrate divergent effects between taxa and that temporal variability in environmental conditions interacts with changes in the thermal mean to mediate microbial responses to global change, with implications for biogeochemical cycling.

Uncertainty of Gridded Precipitation at Local and Continent Scales: A Direct Comparison of Rainfall from SILO and AWAP in Australia - Guobin Fu; Olga Barron; Stephen P. Charles; Michael J. Donn; Thomas G. Van Niel; Geoff Hodgson (Asia-Pacific Journal of Atmospheric Sciences, 2022)

Effects of environmental factors on release amount of heavy metal and structure of microbial community in sediments - T. Wen; H. Zhong; G. Fu; Y. Zhong (International Journal of Environmental Science and Technology, 2022)

Low occurrence of multi‐antimicrobial and heavy metal resistance in Salmonella enterica from wild birds in the United States - Yezhi Fu; Nkuchia M. M'ikanatha; Chris A. Whitehouse; Heather Tate; Andrea Ottesen; Jeffrey M. Lorch; David S. Blehert; Brenda Berlowski‐Zier; Edward G. Dudley (Environmental Microbiology, 2022)
Summary Wild birds are common reservoirs of Salmonella enterica . Wild birds carrying resistant S . enterica may pose a risk to public health as they can spread the resistant bacteria across large spatial scales within a short time. Here, we whole‐genome sequenced 375 S . enterica strains from wild birds collected in 41 U.S. states during 1978–2019 to examine bacterial resistance to antibiotics and heavy metals. We found that Typhimurium was the dominant S . enterica serovar, accounting for 68.3% (256/375) of the bird isolates. Furthermore, the proportions of the isolates identified as multi‐antimicrobial resistant (multi‐AMR: resistant to at least three antimicrobial classes) or multi‐heavy metal resistant (multi‐HMR: resistant to at least three heavy metals) were both 1.87% (7/375). Interestingly, all the multi‐resistant S . enterica ( n = 12) were isolated from water birds or raptors; none of them was isolated from songbirds. Plasmid profiling demonstrated that 75% (9/12) of the multi‐resistant strains carried resistance plasmids. Our study indicates that wild birds do not serve as important reservoirs of multi‐resistant S . enterica strains. Nonetheless, continuous surveillance for bacterial resistance in wild birds is necessary because the multi‐resistant isolates identified in this study also showed close genetic relatedness with those from humans and domestic animals.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Evaluation of Regional Surface Energy Budget Over Ocean Derived From Satellites - Seiji Kato; Fred G. Rose; Fu-Lung Chang; David Painemal; William L. Smith (Frontiers in Marine Science, 2021)
The energy balance equation of an atmospheric column indicates that two approaches are possible to compute regional net surface energy flux. The first approach is to use the sum of surface energy flux components F net,c and the second approach is to use net top-of-atmosphere (TOA) irradiance and horizontal energy transport by the atmosphere F net,t . When regional net energy flux is averaged over the global ocean, F net,c and F net,t are, respectively, 16 and 2 Wm –2 , both larger than the ocean heating rate derived from ocean temperature measurements. The difference is larger than the estimated uncertainty of F net,t of 11 Wm –2 . Larger regional differences between F net,c and F net,t exist over tropical ocean. The seasonal variability of energy flux components averaged between 45°N and 45°S ocean reveals that the surface provides net energy to the atmosphere from May to July. These two examples demonstrates that the energy balance can be used to assess the quality of energy flux data products.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Temperature Significantly Regulates Gene Expressions of Vertebrae Chondrocytes and Osteoblasts in Juvenile Golden Pompano (Trachinotus ovatus) - Mingyang Han; Zhengyi Fu; Rui Yang; Jian G. Qin; Zhenhua Ma (Frontiers in Marine Science, 2021)
To elucidate the possible molecular reaction of vertebral fusion in juvenile golden pompano at high temperature, we examined the changes in growth, vertebral fusion incidence, histological differences and transcription levels of genes related to bone development in juvenile golden pompano at 27 and 33°C for 30 days, respectively. The growth rate of juvenile fish was faster when the water temperature was 33°C, but the incidence of vertebral fusion was higher. Prolonged high water temperature reduced the osteogenic layer in the growth zone of the vertebral endplate and the elastic externa. The endplate growth areas of the fused vertebrae were transformed into cartilage tissue, which was then remodeled into bone. The intervertebral notochord tissue was transformed into bone and the intervertebral space disappeared. In normal phenotypes of vertebrae, short-term high temperature could promote the expression of genes related to cartilage differentiation and maturation, as well as genes related to osteoblastic differentiation. With the increase of culture time, the expression of genes related to cartilage and osteogenesis development was inhibited. In fused vertebrae, cartilage proliferation was enhanced, osteogenic differentiation was inhibited, and matrix mineralization may be enhanced. Genes associated with the development of chondrocytes and osteoblasts in the vertebrae of juvenile Trachinotus ovatus were significantly regulated by temperature and time. The results may contribute to further understanding of the occurrence of vertebral fusion at high temperature.

Robust Estimation Procedure for Autoregressive Models with Heterogeneity - A. Callens; Y.-G. Wang; L. Fu; B. Liquet (Environmental Modeling & Assessment, 2021)

Litter addition and understory removal influenced soil organic carbon quality and mineral nitrogen supply in a subtropical plantation forest - Xiang-Min Fang; G. Geoff Wang; Zhi-Jun Xu; Ying-Ying Zong; Xiu-Lan Zhang; Jian-Jun Li; Huimin Wang; Fu-Sheng Chen (Plant and Soil, 2021)

Mesoscopic Damage and Fracturing of Heterogeneous Brittle Rocks Based on Three-dimensional Polycrystalline Discrete Element Method - Tao Xu; Teng-Fei Fu; Michael J. Heap; Philip G. Meredith; Thomas M. Mitchell; Patrick Baud (Rock Mechanics and Rock Engineering, 2020)

Low Static Shear Modulus Along Foliation and Its Influence on the Elastic and Strength Anisotropy of Poorman Schist Rocks, Homestake Mine, South Dakota - Katherine J. Condon; Hiroki Sone; Herbert F. Wang; J. Ajo-Franklin; T. Baumgartner; K. Beckers; D. Blankenship; A. Bonneville; L. Boyd; S. Brown; J. A. Burghardt; C. Chai; et al. (Rock Mechanics and Rock Engineering, 2020)

Soil accumulation and chemical fractions of Cu in a large and long-term coastal apple orchard, North China - Chuancheng Fu; Chen Tu; Haibo Zhang; Yuan Li; Lianzhen Li; Qian Zhou; Kirk G. Scheckel; Yongming Luo (Journal of Soils and Sediments, 2020)

Transcriptional analysis reveals physiological response to acute acidification stress of barramundi Lates calcarifer (Bloch) in coastal areas - Zhenhua Ma; Xing Zheng; Zhengyi Fu; Siqi Lin; Gang Yu; Jian G. Qin (Fish Physiology and Biochemistry, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Petrogenesis of Jurassic Xietongmen intrusive rocks at the southern margin of the Lhasa terrane: implications for intra-oceanic arc evolution - Y. G. Fu; G. Y. Hu (Australian Journal of Earth Sciences, 2020)

Long-term shifts in abundance of (migratory) crop-feeding and beneficial insect species in northeastern Asia - Jianglong Guo; Xiaowei Fu; Shengyuan Zhao; Xiujing Shen; Kris A. G. Wyckhuys; Kongming Wu (Journal of Pest Science, 2020)
Vast numbers of insects annually engage in trans-latitudinal migration and thereby impact structure and functioning of natural and man-made ecosystems. In eastern Asia, long-distance migration has historically been studied for single insect species rather than diverse species complexes. Here, we assessed migration dynamics of multiple economically important migratory species on an island in the Bohai Strait, China. Drawing upon 15-year trapping records of > 2.5 million specimens, we unveil inter- and intra-annual shifts in the species composition and abundance of migrant individuals. Migrants belonged to 9 orders and 36 families, primarily consisting of Lepidoptera (79% individuals), Odonata (8%), and Coleoptera (4%). Seven crop-feeding noctuids, e.g., Helicoverpa armigera (Hübner), Mythimna separata (Walker), represented 54% of the total trapping records. Trap catches exhibited marked seasonal variation, with the highest capture rate during early fall. Yearly abundance of migratory noctuids was coupled with that of their associated natural enemies. Although overall trap catches did not decrease over the monitoring period, the entire order of Odonata experienced a 14.1% annual rate of decline. Furthermore, 19 out of 108 species exhibited a progressively declining abundance over time, including the cosmopolitan cutworm Agrotis ipsilon (Hufnagel) and the insectivorous dragonfly Pantala flavescens Fabricius. Our work provides unprecedented insights into insect migration dynamics in eastern Asia, helps fine-tune forecasting and early-warning systems of crop pests, and thereby guides integrated pest management within local agro-landscapes. Also, a long-term tracking of migrant insect populations can shine light on the fate of (insect-mediated) ecosystem services and trophic dynamic processes at a macroscale.

Sky islands as foci for divergence of fig trees and their pollinators in southwest China - Jun‐Yin Deng; Rong‐Hua Fu; Stephen G. Compton; Mei Liu; Qin Wang; Chuan Yuan; Lu‐Shui Zhang; Yan Chen (Molecular Ecology, 2020)
The dynamics of populations and their divergence over time have shaped current levels of biodiversity and in the case of the “sky islands” of mountainous southwest (SW) China have resulted in an area of exceptional botanical diversity. Ficus tikoua is a prostrate fig tree subendemic to the area that displays unique intraspecific diversity, producing figs typical of different pollination modes in different parts of its range. By combining climate models, genetic variation in populations of the tree's obligate fig wasp pollinators and distributions of the different plant phenotypes, we examined how this unusual situation may have developed. We identified three genetically distinct groups of a single Ceratosolen pollinator species that have largely parapatric distributions. The complex topography of the region contributed to genetic divergence among the pollinators by facilitating geographical isolation and providing refugia. Migration along elevations in response to climate oscillations further enhanced genetic differentiation of the three pollinator groups. Their distributions loosely correspond to the distributions of the functionally significant morphological differences in the male figs of their host plants, but postglacial expansion of one group has not been matched by spread of its associated plant phenotype, possibly due to a major river barrier. The results highlight how interplay between the complex topography of the “sky island” complex and climate change has shaped intraspecies differentiation and relationships between the plant and its pollinator. Similar processes may explain the exceptional botanical diversity of SW China.

Differential effects of various genetic mouse models of the mechanistic target of rapamycin complex I inhibition on heart failure - Dao-Fu Dai; Yonggang Liu; Nathan Basisty; Pabalu Karunadharma; Somasish G. Dastidar; Ying Ann Chiao; Tony Chen; Richard P. Beyer; Michael T. Chin; Michael Maccoss; Albert R. La Spada; Peter S. Rabinovitch (GeroScience, 2019)

Effects of nutrient addition on foliar phosphorus fractions and their resorption in different-aged leaves of Chinese fir in subtropical China - Fang-Chao Wang; Xiang-Min Fang; G. Geoff Wang; Rong Mao; Xiao-Fan Lin; Huimin Wang; Fu-Sheng Chen (Plant and Soil, 2019)

The effects of simulated deposited nitrogen on nutrient dynamics in decomposing litters across a wide quality spectrum using a 15N tracing technique - Xue-Min Ye; Yang Zhang; Fu-Sheng Chen; G. Geoff Wang; Xiang-Min Fang; Xiao-Fan Lin; Song-Ze Wan; Ping He (Plant and Soil, 2019)

Nitrogen deposition effect on forest litter decomposition is interactively regulated by endogenous litter quality and exogenous resource supply - Fu-Sheng Chen; G. Geoff Wang; Xiang-Min Fang; Song-Ze Wan; Yang Zhang; Chao Liang (Plant and Soil, 2019)

Nutrition and water temperature regulate the expression of heat-shock proteins in golden pompano larvae (Trachinotus ovata, Limmaeus 1758) - Laetitia Allais; Chao Zhao; Mingjun Fu; Jing Hu; Jian G. Qin; Lihua Qiu; Zhenhua Ma (Fish Physiology and Biochemistry, 2019)

Identification of Gangesia oligonchis Roitman & Freze, 1964 (Cestoda: Onchoproteocephalidea) from Tachysurus fulvidraco Richardson in central China: implications for the validity of Gangesia pseudobagrae Chen, 1962 - Pei P. Fu; Wen X. Li; Hong Zou; Dong Zhang; Shan G. Wu; Ming Li; Gui T. Wang; Bing W. Xi (Systematic Parasitology, 2019)

Real-World Variability in the Prediction of Intracranial Aneurysm Wall Shear Stress: The 2015 International Aneurysm CFD Challenge - Kristian Valen-Sendstad; Aslak W. Bergersen; Yuji Shimogonya; Leonid Goubergrits; Jan Bruening; Jordi Pallares; Salvatore Cito; Senol Piskin; Kerem Pekkan; Arjan J. Geers; Ignacio Larrabide; Saikiran Rapaka; et al. (Cardiovascular Engineering and Technology, 2018)

Temperature-related mortality impacts under and beyond Paris Agreement climate change scenarios - Ana Maria Vicedo-Cabrera; Yuming Guo; Francesco Sera; Veronika Huber; Carl-Friedrich Schleussner; Dann Mitchell; Shilu Tong; Micheline de Sousa Zanotti Staglior Coelho; Paulo Hilario Nascimento Saldiva; Eric Lavigne; Patricia Matus Correa; Nicolas Valdes Ortega; et al. (Climatic Change, 2018)

Isometric strength of the hip abductors and external rotators in athletes with and without patellar tendinopathy - Z. J. Zhang; W. C. Lee; G. Y. F. Ng; S. N. Fu (European Journal of Applied Physiology, 2018)

Hydraulic redistribution affects modeled carbon cycling via soil microbial activity and suppressed fire - Congsheng Fu; Guiling Wang; Kenneth Bible; Michael L. Goulden; Scott R. Saleska; Russell L. Scott; Zoe G. Cardon (Global Change Biology, 2018)
Hydraulic redistribution (HR) of water from moist to drier soils, through plant roots, occurs world‐wide in seasonally dry ecosystems. Although the influence of HR on landscape hydrology and plant water use has been amply demonstrated, HR's effects on microbe‐controlled processes sensitive to soil moisture, including carbon and nutrient cycling at ecosystem scales, remain difficult to observe in the field and have not been integrated into a predictive framework. We incorporated a representation of HR into the Community Land Model (CLM4.5) and found the new model improved predictions of water, energy, and system‐scale carbon fluxes observed by eddy covariance at four seasonally dry yet ecologically diverse temperate and tropical AmeriFlux sites. Modeled plant productivity and microbial activities were differentially stimulated by upward HR, resulting at times in increased plant demand outstripping increased nutrient supply. Modeled plant productivity and microbial activities were diminished by downward HR. Overall, inclusion of HR tended to increase modeled annual ecosystem uptake of CO 2 (or reduce annual CO 2 release to the atmosphere). Moreover, engagement of CLM4.5′s ground‐truthed fire module indicated that though HR increased modeled fuel load at all four sites, upward HR also moistened surface soil and hydrated vegetation sufficiently to limit the modeled spread of dry season fire and concomitant very large CO 2 emissions to the atmosphere. Historically, fire has been a dominant ecological force in many seasonally dry ecosystems, and intensification of soil drought and altered precipitation regimes are expected for seasonally dry ecosystems in the future. HR may play an increasingly important role mitigating development of extreme soil water potential gradients and associated limitations on plant and soil microbial activities, and may inhibit the spread of fire in seasonally dry ecosystems.

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Characterization of an expressed Triticum monococcum Glu-A1y gene containing a premature termination codon in its C-terminal coding region - G. Chen; M.H. Zhang; X.J. Liu; J.Y. Fu; H.Y. Li; M. Hao; S.Z. Ning; Z.W. Yuan; Z.H. Yan; B.H. Wu; D.C. Liu; L.Q. Zhang (Cereal Research Communications, 2018)

A cardioid oscillator with asymmetric time ratio for establishing CPG models - Q. Fu; D. H. Wang; L. Xu; G. Yuan (Biological Cybernetics, 2018)

Genome re‐sequencing and simple sequence repeat markers reveal the existence of divergent lineages in the Canadian Puccinia striiformis f. sp. tritici population with extensive DNA methylation - Gurcharn S. Brar; Sajid Ali; Dinah Qutob; Stephen Ambrose; Kun Lou; Ron Maclachlan; Curtis J. Pozniak; Yong‐Bi Fu; Andrew G. Sharpe; Hadley R. Kutcher (Environmental Microbiology, 2018)
Summary Wheat stripe rust, caused by Puccinia striiformis f. sp. tritici ( Pst ), is an important disease in Canada. The worldwide genetic structure of Pst populations have been characterized, excluding Canada. Here, we elucidated the genetic structure of the western Canadian Pst population using molecular markers, revealing the presence of four divergent lineages with predominantly clonal structure. In the worldwide context, two previously reported lineages were identified: PstS0 (22%), representing an old Northwestern‐European and PstS1 (35%), an invasive warm‐temperature adapted. Additionally, two new, unreported lineages, PstPr (9%) and PstS1 ‐related (35%), were detected, which produced more telia than other lineages and had double the number of unique recombination events. The PstPr was a recent invasion, and likely evolved in a diverse, recombinant population as it was closely related to the PstS5 , PstS7 /Warrior, PstS8 /Kranich, and PstS9 lineages originating from sexually recombining populations in the centre of diversity. The DNA methylation analysis revealed DNA‐methyltransferase1‐homologs, providing compelling evidence for epigenetic regulation and as a first report, an average of ∼5%, 5hmC in the Puccinia epigenome merits further investigation. The divergent lineages in the Canadian Pst population with the potential for genetic recombination, as well as epigenetic regulation needs consideration in the context of pathogen adaptation and management.

Ethanol metabolism varies with hypoxia tolerance in ten cyprinid species - Rashpal S. Dhillon; Milica Mandic; Lili Yao; Zhen-Dong Cao; Shi-Jian Fu; Colin J. Brauner; Yuxiang S. Wang; Jeffrey G. Richards (Journal of Comparative Physiology B, 2018)

Effects of rate and application method on the efficacy of metam sodium to reduce clubroot (Plasmodiophora brassicae) of canola - S. F. Hwang; H. U. Ahmed; S. E. Strelkov; Q. Zhou; B. D. Gossen; G. Peng; G. D. Turnbull; H. Fu (European Journal of Plant Pathology, 2018)

Molecular and geochemical perspectives on the influence of CO 2 on calcification in coral cell cultures - Jeana L. Drake; Morgan F. Schaller; Tali Mass; Linda Godfrey; Athena Fu; Robert M. Sherrell; Yair Rosenthal; Paul G. Falkowski (Limnology and Oceanography, 2018)
Understanding the cellular and molecular responses of stony corals to ocean acidification is key to predicting their ability to calcify under projected high CO 2 conditions. Of specific interest are the links between biomineralization proteins and the precipitation of new calcium carbonate (CaCO 3 ), which potentially can provide a better understanding of the biomineralization process. We have assessed the effects of increased CO 2 on the calcification process in cell cultures of the stony coral, Stylophora pistillata , reared in nutrient‐enriched artificial seawater at four pCO 2 levels and two glucose concentrations. Dispersed S. pistillata cells grown at low (400 ppmV) and moderate (700 ppmV) pCO 2 re‐aggregate into proto‐polyps and precipitate CaCO 3 . When grown at pCO 2 levels of 1000 ppmV and 2000 ppmV, the cells up‐regulate genes for two highly acidic proteins as well as a carbonic anhydrase, but down‐regulate long term cadherin protein production and minimize proto‐polyp formation, and exhibit a significant decrease in measurable CaCO 3 precipitation. However, cell cultures precipitate CaCO 3 in all treatments, even at slightly undersaturated conditions (Ω aragonite 11 B of the mineral phase, as a proxy of the pH at the calcifying sites, is out of equilibrium with the ambient seawater medium surrounding the cells and proto‐polyps, suggesting pH is elevated in the micro‐environment of the precipitating mineral. Our results suggest that coral cells possess molecular mechanisms to help compensate for the effects of ocean acidification within the bounds projected in the coming century.

Biogeographic conservation of the cytosine epigenome in the globally important marine, nitrogen‐fixing cyanobacterium Trichodesmium - Nathan G. Walworth; David A. Hutchins; Egor Dolzhenko; Michael D. Lee; Feixue Fu; Andrew D. Smith; Eric A. Webb (Environmental Microbiology, 2017)
Summary Cytosine methylation has been shown to regulate essential cellular processes and impact biological adaptation. Despite its evolutionary importance, only a handful of bacterial, genome‐wide cytosine studies have been conducted, with none for marine bacteria. Here, we examine the genome‐wide, C 5 ‐Methyl‐cytosine (m5C) methylome and its correlation to global transcription in the marine nitrogen‐fixing cyanobacterium Trichodesmium . We characterize genome‐wide methylation and highlight conserved motifs across three Trichodesmium isolates and two Trichodesmium metagenomes, thereby identifying highly conserved, novel genomic signatures of potential gene regulation in Trichodesmium . Certain gene bodies with the highest methylation levels correlate with lower expression levels. Several methylated motifs were highly conserved across spatiotemporally separated Trichodesmium isolates, thereby elucidating biogeographically conserved methylation potential. These motifs were also highly conserved in Trichodesmium metagenomic samples from natural populations suggesting them to be potential in situ markers of m5C methylation. Using these data, we highlight predicted roles of cytosine methylation in global cellular metabolism providing evidence for a ‘core’ m5C methylome spanning different ocean regions. These results provide important insights into the m5C methylation landscape and its biogeochemical implications in an important marine N 2 ‐fixer, as well as advancing evolutionary theory examining methylation influences on adaptation.

Phylogeny and biogeography of the genus Cephalenchus (Tylenchomorpha, Nematoda) - Tiago J. Pereira; Xue Qing; Kuei‐Fu Chang; Manuel Mundo‐Ocampo; Juvenil E. Cares; Erik J. Ragsdale; Chau N. Nguyen; James G. Baldwin (Zoologica Scripta, 2017)
The phylogenetic position of Cephalenchus is enigmatic with respect to other tylench nematodes. In this study, Cephalenchus populations representing 11 nominal species were sampled worldwide for molecular and morphological characterization. Species identification was based on light microscopy ( LM ) and scanning electron microscopy ( SEM ). Molecular analyses were based on the genes (i.e. 18S, 28S, 5.8S) and internal transcribed spacers ( ITS ‐1 and ITS ‐2) of the ribosomal RNA ( rRNA ). Phylogenetic analyses (i.e. full and reduced alignments) of either concatenated or single genes always supported the monophyly of Cephalenchus . A sister relationship between Cephalenchus and Eutylenchus excretorius was recovered by most analyses, although branch support varies depending on the dataset used. The position of Cephalenchus + E. excretorius within Tylenchomorpha nevertheless remains ambiguous, thus highlighting the importance of sampling additional genes as well as taxa. Placement of Cephalenchus + E. excretorius as sister of Tylenchinae or Boleodorinae could not be rejected on the basis of 18S and 28S rRNA genes. Within Cephalenchus , amphidial opening morphology shows congruence with molecular‐based phylogenetic relationships, whereas the number of lines in the lateral field is likely to be a convergent trait. Morphometric analyses clearly distinguished short tail from medium–long tail species, and SEM observations seem to suggest a relation between tail length and amphidial opening. In addition, molecular phylogenies support the non‐monophyly of Cephalenchus cephalodiscus , Cephalenchus cylindricus , Cephalenchus daisuce and Cephalenchus leptus . The known extent of Cephalenchus diversity is increased with the inclusion of two new species, and the biogeography of the genus is discussed.

Alterations in mechanical properties of the patellar tendon is associated with pain in athletes with patellar tendinopathy - W. C. Lee; Z. J. Zhang; L. Masci; G. Y. F. Ng; Siu Ngor Fu (European Journal of Applied Physiology, 2017)

Perfluoroalkyl substances with isomer analysis in umbilical cord serum in China - Ya-Zhi Zhang; Xiao-Wen Zeng; Zhengmin Qian; Michael G. Vaughn; Sarah Dee Geiger; Li-Wen Hu; Long Lu; Chuanxi Fu; Guang-Hui Dong (Environmental Science and Pollution Research, 2017)

Differences between serum polar lipid profiles of male and female rheumatoid arthritis patients in response to glucocorticoid treatment - Junzeng Fu; Bart V. J. Cuppen; Paco M. J. Welsing; Herman van Wietmarschen; Amy C. Harms; Ruud Berger; Slavik Koval; Ruth D. E. Fritsch-Stork; Johannes W. J. Bijlsma; Thomas Hankemeier; Jan van der Greef; Floris P. J. G. Lafeber (Inflammopharmacology, 2016)

High-density marker profiling confirms ancestral genomes of Avena species and identifies D-genome chromosomes of hexaploid oat - Honghai Yan; Wubishet A. Bekele; Charlene P. Wight; Yuanying Peng; Tim Langdon; Robert G. Latta; Yong-Bi Fu; Axel Diederichsen; Catherine J. Howarth; Eric N. Jellen; Brian Boyle; Yuming Wei; et al. (Theoretical and Applied Genetics, 2016)

Seed predators can increase nectar volumes in an alpine daisy: but do the insects benefit? - Junpeng Mu; Yan Chen; Yulian Yang; Ronghua Fu; Hui Wang; Stephen G. Compton (Plant Ecology, 2016)

Parasitism Performance of Tetrastichus brontispae Ferriere over the Coconut Hispine Beetle, Brontispa longissima (Gestro) - K Liu; B L Fu; J R Lin; Y G Fu; Z Q Peng; Q A Jin; L D Tang (Neotropical Entomology, 2016)

Characterization of pollution transport into Texas using OMI and TES satellite, GIS and in situ data, and HYSPLIT back trajectory analyses: implications for TCEQ State Implementation Plans - D. Bella; J. Culpepper; J. Khaimova; N. Ahmed; Adam Belkalai; I. Arroyo; J. Andrews; S. Gentle; S. Emmanuel; M. Lahmouh; J. Ealy; Zayna King; et al. (Air Quality, Atmosphere & Health, 2016)

Poisonings Associated with Intubation: US National Poison Data System Exposures 2000–2013 - G. A. Beauchamp; S. L. Giffin; B. Z. Horowitz; A. L. Laurie; R. Fu; R. G. Hendrickson (Journal of Medical Toxicology, 2016)

The role of salinity in seed maturation of the euhalophyte Suaeda salsa - J. C. Zhou; T. T. Fu; N. Sui; J. R. Guo; G. Feng; J. L. Fan; J. Song (Plant Biosystems, 2016)

Meta-analyses of structural regional cerebral effects in type 1 and type 2 diabetes - Calum D. Moulton; Sergi G. Costafreda; Paul Horton; Khalida Ismail; Cynthia H. Y. Fu (Brain Imaging and Behavior, 2015)

Effects of habitual loading on patellar tendon mechanical and morphological properties in basketball and volleyball players - Z. J. Zhang; G. Y. F. Ng; S. N. Fu (European Journal of Applied Physiology, 2015)

Effect of Biochar in Cadmium Availability and Soil Biological Activity in an Anthrosol Following Acid Rain Deposition and Aging - H. Lu; Z. Li; S. Fu; A. Méndez; G. Gascó; J. Paz-Ferreiro (Water, Air, & Soil Pollution, 2015)

Efficiency and Accuracy Verification of the Explicit Numerical Manifold Method for Dynamic Problems - X. L. Qu; Y. Wang; G. Y. Fu; G. W. Ma (Rock Mechanics and Rock Engineering, 2015)

Coupling of postural activity with motion of a ship at sea - Manuel Varlet; Benoît G. Bardy; Fu-Chen Chen; Cristina Alcantara; Thomas A. Stoffregen (Experimental Brain Research, 2015)

Influence of Constant Temperature on Development and Reproduction of Encarsia guadeloupae Viggiani (Hymenoptera: Aphelinidae), a Parasitoid of the Spiraling Whitefly Aleurodicus dispersus Russell (Hemiptera: Aleyrodidae) - J Y Chen; L M Niu; L Li; D Y Han; Y G Fu (Neotropical Entomology, 2015)

Aberrant methylation of miR-34b is associated with long-term shiftwork: a potential mechanism for increased breast cancer susceptibility - Ran Liu; Daniel I. Jacobs; Johnni Hansen; Alan Fu; Richard G. Stevens; Yong Zhu (Cancer Causes & Control, 2015)

Effects of fasting and feeding on the fast‐start swimming performance of southern catfish Silurus meridionalis - G. J. Yan; X. K. He; Z. D. Cao; S. J. Fu (Journal of Fish Biology, 2015)
This study investigated the effects of fasting and feeding on the fast‐start escape swimming performance of juvenile southern catfish Silurus meridionalis , a sit‐and‐wait forager that encounters extreme fasting and famine frequently during its lifespan. Ten to 30 days of fasting resulted in no significant change in most of the variables measured in the fast‐start response except a 20–30% decrease in the escape distance during the first 120 ms ( D 120ms ) relative to the control group (48 h after feeding). The ratio of the single‐bend ( SB ) response (lower energetic expenditure) to the double‐bend ( DB ) response increased significantly from 0% in the control group to 75 and 82·5% in the 20 and 30 day fasting groups, respectively. Satiated feeding (25% of body mass) resulted in a significantly lower (36·6%) maximum linear velocity ( V max ) and a significantly lower (43·3%) D 120ms than in non‐fed fish (control group, 48 h after feeding). Half‐satiated feeding (12·5% of body mass), however, showed no significant effects on any of the measured variables of the fast‐start response relative to control fish. It is suggested that the increase in the ratio of SB : DB responses with fasting in S. meridionalis may reflect a trade‐off between energy conservation and maintaining high V max , while variables of fast‐start performance were more sensitive to feeding than fasting might be an adaptive strategy to their foraging mode and food availability in their habitat.

mTOR ATP-competitive inhibitor INK128 inhibits neuroblastoma growth via blocking mTORC signaling - Huiyuan Zhang; Jun Dou; Yang Yu; Yanling Zhao; Yihui Fan; Jin Cheng; Xin Xu; Wei Liu; Shan Guan; Zhenghu Chen; Yan shi; Roma Patel; et al. (Apoptosis, 2015)

Accuracy and Reproducibility of Patient-Specific Hemodynamic Models of Stented Intracranial Aneurysms: Report on the Virtual Intracranial Stenting Challenge 2011 - S. Cito; A. J. Geers; M. P. Arroyo; V. R. Palero; J. Pallarés; A. Vernet; J. Blasco; L. San Román; W. Fu; A. Qiao; G. Janiga; Y. Miura; et al. (Annals of Biomedical Engineering, 2015)

Field Evaluation of Different Wavelengths Light-Emitting Diodes as Attractants for Adult Aleurodicus dispersus Russell (Hemiptera: Aleyrodidae) - L X Zheng; Y Zheng; W J Wu; Y G Fu (Neotropical Entomology, 2014)

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)

Water Footprint of Cereals and Vegetables for the Beijing Market - Jing Huang; Bradley G. Ridoutt; Hailin Zhang; Changchun Xu; Fu Chen (Journal of Industrial Ecology, 2014)
Summary Beijing is situated in water‐scarce northern China, where there is a history of policies aimed at constraining local agricultural water use to meet the increasing urban water demand. This has led to a change in local crop production and subsequent effects in terms of the importation of cereals and vegetables grown in other parts of China. The dilemma is that local policies designed to improve Beijing's water resources situation may have the unintended consequence of increasing water stress in other regions. In this article, life cycle assessment approaches were used to model both consumptive and degradative water use for the major cereals and vegetables consumed in Beijing, enabling comparison of local and imported supplies. In the Beijing region, cropping cereals rather than intensive vegetables in greenhouses could reduce local blue water consumption by 7,216 cubic meters per hectare per year (m 3 ha −1 yr −1 ) and nitrogen pollution by 45 kg ha −1 yr −1 . However, depending on how the local food shortfall is balanced by imported food, shifts in cropping pattern in Beijing have the potential to cause either an improvement or exacerbation of the nationwide water stress situation (e.g., −42% to 4% for water scarcity footprint). As such, local policy making regarding agricultural land and water use needs to consider the wider food production context. This situation in Beijing is likely to be representative of the challenge facing many of the world's large and mega‐sized cities, where a sustainable means of increasing food supply must be found.

A Factorial-based Dynamic Analysis Method for Reservoir Operation Under Fuzzy-stochastic Uncertainties - D. Z. Fu; Y. P. Li; G. H. Huang (Water Resources Management, 2013)

Divergent Effects of Sulforaphane on Basal and Glucose-Stimulated Insulin Secretion in β-Cells: Role of Reactive Oxygen Species and Induction of Endogenous Antioxidants - Jingqi Fu; Qiang Zhang; Courtney G. Woods; Hongzhi Zheng; Bei Yang; Weidong Qu; Melvin E. Andersen; Jingbo Pi (Pharmaceutical Research, 2013)

Scanning Electron Microscopy Studies of the Antennal Sensilla of Metaphycus parasaissetiae Zhang & Huang (Hymenoptera: Encyrtidae) - H Zhou; W J Wu; F P Zhang; Y G Fu (Neotropical Entomology, 2013)

Three genetic systems controlling growth, development and productivity of rice (Oryza sativa L.): a reevaluation of the ‘Green Revolution’ - Fan Zhang; Yun-Zhu Jiang; Si-Bin Yu; J. Ali; A. H. Paterson; G. S. Khush; Jian-Long Xu; Yong-Ming Gao; Bin-Ying Fu; R. Lafitte; Zhi-Kang Li (Theoretical and Applied Genetics, 2013)

Ribonuclease 4 protects neuron degeneration by promoting angiogenesis, neurogenesis, and neuronal survival under stress - Shuping Li; Jinghao Sheng; Jamie K. Hu; Wenhao Yu; Hiroko Kishikawa; Miaofen G. Hu; Kaori Shima; David Wu; Zhengping Xu; Winnie Xin; Katherine B. Sims; John E. Landers; et al. (Angiogenesis, 2013)

Ultrastructural analysis of flagellar development in plurilocular sporangia of Ectocarpus siliculosus (Phaeophyceae) - Gang Fu; Chikako Nagasato; Toshiaki Ito; Dieter G. Müller; Taizo Motomura (Protoplasma, 2013)

Characterization and expression of Cd8 molecules in mandarin fish Siniperca chuatsi - Z. Guo; G. L. Wang; J. P. Fu; P. Nie (Journal of Fish Biology, 2013)
The full‐length complementary DNA (cDNA) sequences encoding cd8α and cd8β molecules were sequenced and characterized from mandarin fish Siniperca chuatsi . Conserved motifs and residues were found to be present in derived peptides of the Cd8 molecules. For example, WXR motif, DXGXYXC motif, and four cysteine residues were present in the extracellular region of the Cd8 protein. Threonine, serine and proline residues involved in multiple O ‐linked glycosylation events were located in the membrane proximal hinge region. The common CPH motif in the cytoplasmic tail was detected similar to other teleost Cd8 molecules. Different from those in mammals, S. chuatsi Cd8 sequences have many extra cysteine residues (C149 in Cd8 α sequence and C46, C51 and C158 in Cd8 β sequence), which also exist in other teleost Cd8 molecules. Real‐time polymerase chain reaction (RT‐PCR) and Western blot analyses revealed that the thymus had the highest expression of cd8 messenger (m)RNA and protein. After stimulated with phytohaemagglutinin, polyriboinsine‐polyribocyaidylic acid and concanavalin A (ConA), the expression level of cd8 mRNA increased significantly in head‐kidney lymphocytes at 4 and 8 h, but decreased to normal level at 12 h. Similarly, stimulation with ConA in vivo also led to an increase in the cd8 mRNA level in the spleen. Immunohistochemistry analysis demonstrated that Cd8 α ‐positive cells can be detected in the thymus, spleen and intestine by using polyclonal anti‐Cd8 α antibody.

Arsenic accumulation and distribution in the tissues of inbred lines in maize (Zea mays L.) - Z. H. Liu; W. H. Li; H. Y. Qi; G. L. Song; D. Ding; Z. Y. Fu; J. B. Liu; J. H. Tang (Genetic Resources and Crop Evolution, 2012)

An enormous Jurassic turtle bone bed from the Turpan Basin of Xinjiang, China - Oliver Wings; Márton Rabi; Jörg W. Schneider; Leonie Schwermann; Ge Sun; Chang-Fu Zhou; Walter G. Joyce (The Science of Nature, 2012)

A fuzzy-Markov-chain-based analysis method for reservoir operation - D. Z. Fu; Y. P. Li; G. H. Huang (Stochastic Environmental Research and Risk Assessment, 2012)

Fine mapping of 14q24.1 breast cancer susceptibility locus - Phoebe Lee; Yi-Ping Fu; Jonine D. Figueroa; Ludmila Prokunina-Olsson; Jesus Gonzalez-Bosquet; Peter Kraft; Zhaoming Wang; Kevin B. Jacobs; Meredith Yeager; Marie-Josèphe Horner; Susan E. Hankinson; Amy Hutchinson; et al. (Human Genetics, 2012)

Molecular cloning, characterization and expression analysis of B cell translocation gene 1 in grass carp Ctenopharyngodon idella - Y. J. Fu; F. G. Huang; T. Yuan; J. R. Gu; G. Q. Luo; H. Xu (Journal of Fish Biology, 2012)
An expressed sequence tag (EST) of B cell translocation gene (BTG) 1 ( gcbtg1 ) was obtained from a grass carp Ctenopharyngodon idellus intestinal complementary (c)DNA library and the full‐length cDNA sequence was acquired by rapid amplification of cDNA ends (RACE) technology. The predicted Gcbtg1 protein contains the box A and box B motifs which characterized the BTG and transducer of ERBB2 (TOB) family. Multiple alignment analysis reveals that Gcbtg1 shares an overall identity of 65–94% with Gcbtg1s of other vertebrates. Real‐time quantitative PCR analysis reveals that the highest expression level of gcbtg1 was detected in liver and the lowest in muscle. Western blotting analysis indicates that the immunological cross‐reactivity occurs between C. idella and human Homo sapiens BTG1 protein. A 1008 bp 5′‐flanking region sequence was cloned and analysed.

Genetic Diversity of Kenyan Potato Germplasm Revealed by Simple Sequence Repeat Markers - Charles Lung’aho; George N. Chemining’wa; Yong-Bi Fu; Solomon I. Shibairo; Margaret J. Hutchinson; Humberto G. Paniagua (American Journal of Potato Research, 2011)

Portal protein diversity and phage ecology - Matthew B. Sullivan; Maureen L. Coleman; Vanessa Quinlivan; Jessica E. Rosenkrantz; Alicia S. DeFrancesco; G. Tan; Ross Fu; Jessica A. Lee; John B. Waterbury; Joseph P. Bielawski; Sallie W. Chisholm (Environmental Microbiology, 2011)

Integrin β4 Signaling Promotes Mammary Tumor Cell Adhesion to Brain Microvascular Endothelium by Inducing ErbB2-Mediated Secretion of VEGF - Jie Fan; Bin Cai; Min Zeng; Yanyan Hao; Filippo G. Giancotti; Bingmei M. Fu (Annals of Biomedical Engineering, 2011)

An AEM study of garnet clinopyroxenite from the Sulu ultrahigh-pressure terrane: formation mechanisms of oriented ilmenite, spinel, magnetite, amphibole and garnet inclusions in clinopyroxene - Shyh-Lung Hwang; Tzen-Fu Yui; Hao-Tsu Chu; Pouyan Shen; Ru-Yuan Zhang; Juhn G. Liou (Contributions to Mineralogy and Petrology, 2011)

Genomic sequence of an avian paramyxovirus type 1 strain isolated from Muscovy duck (Cairina moschata) in China - S.-H. Shi; Yu Huang; S.-J. Cui; L.-F. Cheng; G.-H. Fu; X. Li; Z. Chen; C.-X. Peng; F. Lin; J.-S. Lin; Jing-Liang Su (Archives of Virology, 2011)

A new long terminal repeat (LTR) sequence allows to identify J genome from JS and St genomes of Thinopyrum intermedium - Z. X. Tang; Z. J. Yang; S. L. Fu; M. Y. Yang; G. R. Li; H. Q. Zhang; F. Q. Tan; Zhenglong Ren (Journal of Applied Genetics, 2011)

Timing and duration of growth hiatuses in mid Holocene massive Porites corals from the northern South China Sea - Ke‐Fu Yu; Jian‐Xin Zhao; Michael G. Lawrence; Yuexing Feng (Journal of Quaternary Science, 2010)
Growth hiatuses in massive corals are usually indicative of past ecological or environmental stresses. Among 37 fossil Porites colonies surveyed from the reef flat of Dadonghai fringing reef at Sanya, Hainan Island, northern South China Sea, seven of them were found to show clear evidence of past mortality, representing a population of ∼19%. Among these samples, two of them (SYO‐13 and SYO‐28) display clear growth hiatuses reflecting mortality followed by subsequent recruitment, and five others exhibit a well‐preserved mortality surface and no subsequent recruitment. The growth hiatuses were dated using high‐precision thermal ionisation mass spectrometry U‐series techniques. The age results suggest all the dated corals formed and died in the mid Holocene. Multiple dates below the growth hiatuses suggest that SYO‐13 and SYO‐28 died at 6298 ± 11 and 6929 ± 19 a BP (i.e. years before AD 1950), respectively. Multiple dates above the growth hiatuses indicate that growth in SYO‐13 and SYO‐28 resumed at 6257 ± 14 and 6898 ± 20 a BP, respectively. The calculated durations of growth hiatuses are therefore 41 ± 18 a for SYO‐13 and 31 ± 28 a for SYO‐28, respectively, implying growth resumed within decades after the mortality events. U‐series dating of four other samples with dead heads suggests that they died at 6035 ± 53, 6059 ± 23, 6127 ± 22 and 6474 ± 24 a BP, respectively. In addition, using solution inductively coupled plasma mass spectrometry (ICP‐MS), monthly resolution Sr/Ca and Mg/Ca ratios were determined for the annual growth bands below and above the growth hiatuses for three of the dated samples. The Sr/Ca and Mg/Ca profiles indicate that the three corals probably died in different seasons (from spring to autumn), and the mortality appears to be unrelated to anomalous sea surface temperature‐induced bleaching. Copyright © 2010 John Wiley & Sons, Ltd.

OSTM/Jason-2: Assessment of the System Performances (Ocean Surface Topography Mission: OSTM) - G. Zaouche; J. Perbos; T. Lafon; V. Couderc; J. Lambin; J. D. Desjonqueres; C. Jayles; E. Jurado; P. Vaze; L.-L. Fu; S. Brown; F. Parisot; et al. (Marine Geodesy, 2010)

An observational and modeling study of a sea fog event over the Yellow Sea on 1 August 2003 - Gang Fu; Pengyuan Li; Joseph G. Crompton; Jingtian Guo; Shanhong Gao; Suping Zhang (Meteorology and Atmospheric Physics, 2010)

QTL detection for grain oil and starch content and their associations in two connected F2:3 populations in high-oil maize - Y. Z. Wang; J. Z. Li; Y. L. Li; M. G. Wei; X. H. Li; J. F. Fu (Euphytica, 2010)

Phylogenetic network of Linum species as revealed by non-coding chloroplast DNA sequences - Yong-Bi Fu; Robin G. Allaby (Genetic Resources and Crop Evolution, 2010)

Mapping of QTLs detected in a Brassica napus DH population for resistance to Sclerotinia sclerotiorum in multiple environments - Xiangrui Yin; Bin Yi; Wei Chen; Weijie Zhang; Jinxing Tu; W. G. Dilantha Fernando; Tingdong Fu (Euphytica, 2010)

Comparison of approaches for efficient gene silencing induced by microRNA-based short hairpin RNA and indicator gene expression - Z. X. Shan; Q. X. Lin; C. Y. Deng; Z. L. Zhou; H. H. Tan; Y. H. Fu; X. H. Li; J. N. Zhu; L. P. Mai; S. J. Kuang; S. G. Lin; X. Y. Yu (Molecular Biology Reports, 2010)

Effect of polymorphism in the leukemia inhibitory factor gene on litter size in Large White pigs - H. C. Lin; G. F. Liu; A. G. Wang; L. J. Kong; X. F. Wang; J. L. Fu (Molecular Biology Reports, 2009)

Differential expression of candidate genes for lignin biosynthesis under drought stress in maize leaves - Y. Hu; W. Ch. Li; Y. Q. Xu; G. J. Li; Y. Liao; F. -L. Fu (Journal of Applied Genetics, 2009)

Dent corn genetic background influences QTL detection for grain yield and yield components in high-oil maize - Y. L. Li; X. H. Li; J. Z. Li; J. F. Fu; Y. Z. Wang; M. G. Wei (Euphytica, 2009)

Detrital zircon evidence for the antiquity of Taiwan - Ching-Ying Lan; Tadashi Usuki; Kuo-Lung Wang; Tzen-Fu Yui; Kazuaki Okamoto; Yuan-Hsi Lee; Takafumi Hirata; Yoshitaka Kon; Yuji Orihashi; Juhn G. Liou; Chun-Sun Lee (Geosciences Journal, 2009)

Early Paleozoic medium-pressure metamorphism in central Vietnam: evidence from SHRIMP U-Pb zircon ages - Tadashi Usuki; Ching-Ying Lan; Tzen-Fu Yui; Yoshiyuki Iizuka; Tich Van Vu; Tuan Anh Tran; Kazuaki Okamoto; Joseph L. Wooden; Juhn G. Liou (Geosciences Journal, 2009)

Lipid rafts play an important role in the vesicular stomatitis virus life cycle - W. Wang; Y. J. Fu; Y. G. Zu; N. Wu; J. Reichling; T. Efferth (Archives of Virology, 2009)

Genetic analysis of H3 subtype influenza viruses isolated from domestic ducks in northern China during 2004–2005 - Juan Pu; Qin-Fang Liu; Ying-Ju Xia; Yu-Lei Fan; Earl G. Brown; Fu-Lin Tian; Jin-Hua Liu (Virus Genes, 2009)

Hepatic and extrahepatic expression of estrogen-responsive genes in male adult zebrafish (Danio rerio) as biomarkers of short-term exposure to 17β-estradiol - Yuanxiang Jin; Wanyuan Wang; G. Daniel Sheng; Weiping Liu; Zhengwei Fu (Environmental Monitoring and Assessment, 2008)

Portal protein diversity and phage ecology - Matthew B. Sullivan; Maureen L. Coleman; Vanessa Quinlivan; Jessica E. Rosenkrantz; Alicia S. DeFrancesco; G. Tan; Ross Fu; Jessica A. Lee; John B. Waterbury; Joseph P. Bielawski; Sallie W. Chisholm (Environmental Microbiology, 2008)
Summary Oceanic phages are critical components of the global ecosystem, where they play a role in microbial mortality and evolution. Our understanding of phage diversity is greatly limited by the lack of useful genetic diversity measures. Previous studies, focusing on myophages that infect the marine cyanobacterium Synechococcus , have used the coliphage T4 portal‐protein‐encoding homologue, gene 20 ( g20 ), as a diversity marker. These studies revealed 10 sequence clusters, 9 oceanic and 1 freshwater, where only 3 contained cultured representatives. We sequenced g20 from 38 marine myophages isolated using a diversity of Synechococcus and Prochlorococcus hosts to see if any would fall into the clusters that lacked cultured representatives. On the contrary, all fell into the three clusters that already contained sequences from cultured phages. Further, there was no obvious relationship between host of isolation, or host range, and g20 sequence similarity. We next expanded our analyses to all available g20 sequences (769 sequences), which include PCR amplicons from wild uncultured phages, non‐PCR amplified sequences identified in the Global Ocean Survey (GOS) metagenomic database, as well as sequences from cultured phages, to evaluate the relationship between g20 sequence clusters and habitat features from which the phage sequences were isolated. Even in this meta‐data set, very few sequences fell into the sequence clusters without cultured representatives, suggesting that the latter are very rare, or sequencing artefacts. In contrast, sequences most similar to the culture‐containing clusters, the freshwater cluster and two novel clusters, were more highly represented, with one particular culture‐containing cluster representing the dominant g20 genotype in the unamplified GOS sequence data. Finally, while some g20 sequences were non‐randomly distributed with respect to habitat, there were always numerous exceptions to general patterns, indicating that phage portal proteins are not good predictors of a phage's host or the habitat in which a particular phage may thrive.

Mixed messages in iron oxide–copper–gold systems of the Cloncurry district, Australia: insights from PIXE analysis of halogens and copper in fluid inclusions - Timothy Baker; Roger Mustard; Bin Fu; Patrick J. Williams; Guoyi Dong; Louise Fisher; Geordie Mark; Chris G. Ryan (Mineralium Deposita, 2008)

Radiation-Guided P-Selectin Antibody Targeted to Lung Cancer - G. Hariri; Y. Zhang; A. Fu; Z. Han; M. Brechbiel; M. N. Tantawy; T. E. Peterson; R. Mernaugh; D. Hallahan (Annals of Biomedical Engineering, 2008)

Response of Brassica napus and B. juncea germplasm from Australia, China and India to Australian populations of Leptosphaeria maculans - C. X. Li; N. Wratten; P. A. Salisbury; W. A. Burton; T. D. Potter; G. Walton; Hua Li; K. Sivasithamparam; Surinder S. Banga; Shashi Banga; D. Singh; S. Y. Liu; et al. (Australasian Plant Pathology, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Sesquiterpene lactones from Saussurea alata - G. Ren; Z. M. Yu; Y. L. Chen; S. H. Wu; C. X. Fu (Natural Product Research, 2007)

Geochemical evidence for the variation of historical seabird population on Dongdao Island of the South China Sea - X. D. Liu; S. P. Zhao; L. G. Sun; H. H. Luo; X. B. Yin; Z. Q. Xie; Y. H. Wang; K. X. Liu; X. H. Wu; X. F. Ding; D. P. Fu (Journal of Paleolimnology, 2006)

Genetic Variation and Relationships of Pedigree-Known Oat, Wheat, and Barley Cultivars Releaved by Bulking and Single-Plant Sampling - Yong-Bi Fu; William G. Legge; John M. Clarke; Ken W. Richards (Genetic Resources and Crop Evolution, 2006)

Successful implantation of intravenously administered stem cells correlates with severity of inflammation in murine myocarditis - Sohail Malek; Emel Kaplan; Ju-Feng Wang; Qingen Ke; Jamal S. Rana; Yu Chen; Bilal G. Rahim; Ma Li; Qin Huang; Yong-Fu Xiao; Freek W. A. Verheugt; James P. Morgan; et al. (Pflügers Archiv - European Journal of Physiology, 2006)

Seasonal Variation of the Particle Size Distribution of n-Alkanes and Polycyclic Aromatic Hydrocarbons (PAHs) in Urban Aerosol of Guangzhou, China - X. L. Tang; X. H. Bi; G. Y. Sheng; J. H. Tan; J. M. FU (Environmental Monitoring and Assessment, 2006)

Evidence of the domestication history of flax (Linum usitatissimum L.) from genetic diversity of the sad2 locus - Robin G. Allaby; Gregory W. Peterson; David Andrew Merriwether; Yong-Bi Fu (Theoretical and Applied Genetics, 2005)

Effects of ketamine on prefrontal and striatal regions in an overt verbal fluency task: a functional magnetic resonance imaging study - Cynthia H. Y. Fu; Kathryn M. Abel; Matthew P. G. Allin; David Gasston; Sergi G. Costafreda; John Suckling; Steve C. R. Williams; Philip K. McGuire (Psychopharmacology, 2005)

Mercury Accumulation and Distribution in Medaka after the Exposure to Sublethal Levels of Methylmercury - C.-Y. Liao; Q.-F. Zhou; J.-B. Shi; J.-J. Fu; G.-B. Jiang (Bulletin of Environmental Contamination and Toxicology, 2005)

Postglacial colonization of the Tibetan plateau inferred from the matrilineal genetic structure of the endemic red‐necked snow finch, Pyrgilauda ruficollis - YAN HUA QU; PER G. P. ERICSON; FU MIN LEI; SHOU HSIEN LI (Molecular Ecology, 2005)
Most phylogeographical studies of postglacial colonization focus on high latitude locations in the Northern Hemisphere. Here, we studied the phylogeographical structure of the red‐necked snow finch Pyrgilauda ruficollis , an endemic species of the Tibetan plateau. We analysed 879 base pairs (bp) of the mitochondrial cytochrome b gene and 529 bp of the control region in 41 birds from four regional groups separated by mountain ranges. We detected 34 haplotypes, 31 of which occurred in a single individual and only three of which were shared among sampling sites within regional groups or among regional groups. Haplotype diversity was high ( h = 0.94); nucleotide diversity was low (ð = 0.00415) and genetic differentiation was virtually non‐existent. Analyses of mismatch distributions and geographically nested clades yielded results consistent with contiguous range expansion, and the expansion times were estimated as 0.07–0.19 million years ago (Ma). Our results suggest that P. ruficollis colonized the Tibetan plateau after the extensive glacial period (0.5–0.175 Ma), expanding from the eastern margin towards the inner plateau. Thus, in contrast to many of the postglacial phylogeographical structures known at high latitudes, this colonization occurred without matrilineal population structuring. This might be due to the short glacial cycles typical of the Tibetan plateau, adaptation of P. ruficollis to cold conditions, or refugia and colonized habitat being semicontinuous and thus promoting population mixing.

Specific amino acid restriction inhibits attachment and spreading of human melanoma via modulation of the integrin/focal adhesion kinase pathway and actin cytoskeleton remodeling - Ya-Min Fu; Hui Zhang; Mingjie Ding; Yi-Qi Li; Xing Fu; Zu-Xi Yu; Gary G. Meadows (Clinical & Experimental Metastasis, 2005)

Simulation Studies of High-Latitude Magnetospheric Boundary Dynamics - Q. Q. Shi; Z. Y. Pu; H. Zhang; S. Y. Fu; C. J. Xiao; Q. -G. Zong; T. A. Fritz; Z. X. Liu (Surveys in Geophysics, 2005)

Energetic Particles Observed in the CUSP Region During a Storm Recovery Phase - S. Y. Fu; Q. G. Zong; Z. Y. Pu; C. J. Xiao; A. Korth; P. Daly; H. Reme (Surveys in Geophysics, 2005)

Multiple Flux Rope Events at the High-Latitude Magnetopause: Cluster/Rapid Observation on 26 January, 2001 - Z. Y. Pu; Q. -G. Zong; T. A. Fritz; C. J. Xiao; Z. Y. Huang; S. Y. Fu; Q. Q. Shi; M. W. Dunlop; K. -H. Glassmeier; A. Balogh; P. Daly; H. Reme; et al. (Surveys in Geophysics, 2005)

Kokchetavite: a new potassium-feldspar polymorph from the Kokchetav ultrahigh-pressure terrane - Shyh-Lung Hwang; Pouyan Shen; Hao-Tsu Chu; Tzen-Fu Yui; Juhn G. Liou; Nikolay V. Sobolev; Ru-Yuan Zhang; Vladislav S. Shatsky; Anton A. Zayachkovsky (Contributions to Mineralogy and Petrology, 2004)

An efficient mannose selection protocol for tomato that has no adverse effect on the ploidy level of transgenic plants - Marina Sigareva; Rody Spivey; Michael G. Willits; Catherine M. Kramer; Yin-Fu Chang (Plant Cell Reports, 2004)

Amazonian climate: results and future research - J. H. C. Gash; C. Huntingford; J. A. Marengo; R. A. Betts; P. M. Cox; G. Fisch; R. Fu; A. W. Gandu; P. P. Harris; L. A. T. Machado; C. von Randow; M. A. Silva Dias (Theoretical and Applied Climatology, 2004)

Segmental nerve conduction velocity in vibration-exposed shipyard workers - M. Cherniack; A. J. Brammer; R. Lundstrom; J. Meyer; T. F. Morse; G. Nealy; T. Nilsson; D. Peterson; E. Toppilla; N. Warren; R. W. Fu; H. Bruneau (International Archives of Occupational and Environmental Health, 2004)

Concentration Profiles of Acidic and Basic Air Pollutants Around an Industrial Park of Taiwan - Chuen-Jinn Tsai; Shankar G. Aggarwal; Chung-Tso Chang; I-Fu Hung (Water, Air, & Soil Pollution, 2004)

Parameterization of effective ice particle size for high‐latitude clouds - Faisal S. Boudala; George A. Isaac; Qiang Fu; Stewart G. Cober (International Journal of Climatology, 2002)
A parameterization has been developed for mean effective size D ge in terms of ice water content (IWC) and temperature using in situ measurements of ice crystal spectra, cloud particle shapes and particle cross‐sectional area A from four research projects conducted in latitudes north of 45° N. The cloud microphysical measurements were made using PMS 2D optical probes, a PMS forward scattering spectrometer probe (FSSP), and Nevzorov total water and liquid water content probes. The IWCs derived from particle spectra using three different methods were compared with IWC measured with the Nevzorov probe (IWC Nev ). The contribution of small particles to the total mass was estimated by integrating a gamma distribution function that was fitted to match the measured FSSP concentrations. The D ge was calculated from the derived IWC and total cross‐sectional area per unit volume A c . This analysis indicates that there are significant differences among the schemes used to derive the IWC. It was found that the IWC derived based on the Cunningham scheme and IWC Nev have the highest correlation: r 2 = 0.78. After considering small particles, the derived IWC almost matched the IWC Nev . The average estimated contribution of small particles to the A c was 43%. The average estimated contribution of small particles to the total IWC, however, was 20%. Since D ge is directly proportional to the ratio IWC/ A c , the addition of small particles reduced the derived D ge considerably. The largest changes in D ge associated with small particles, however, occur at the coldest temperature and at low IWC, reaching up to 45% for temperatures less than −25° C. Generally, D ge and IWC increase with increasing temperature. Good agreement between the parameterized D ge and derived D ge from measurements were found when small particles were included. Copyright © 2002 Royal Meteorological Society.

Distribution of Organochlorine Pesticides in a Sediment Profile of the Pearl River Estuary - X. D. Li; B. X. Mai; G. Zhang; G. Y. Sheng; J. M. Fu; S. M. Pan; O. W. H. Wai; Y. S. Li (Bulletin of Environmental Contamination and Toxicology, 2001)

Attenuated Lapinized Chinese Strain of Classical Swine Fever Virus: Complete Nucleotide Sequence and Character of 3′-Noncoding Region - H. X. Wu; J. F. Wang; C. Y. Zhang; L. Z. Fu; Z. S. Pan; N. Wang; P. W. Zhang; W. G. Zhao (Virus Genes, 2001)

Mobility of components in metasomatic transformation and partial melting of gneisses: an example from Sri Lanka - L. L. Perchuk; O. G. Safonov; T. V. Gerya; B. Fu; D. E. Harlov (Contributions to Mineralogy and Petrology, 2000)

Genetic susceptibility to pre-eclampsia and chromosome 7q36 - G. Guo; J.A. Lade; A.N. Wilton; E.K. Moses; M. Grehan; Y. Fu; H. Qiu; D.W. Cooper; S.P. Brennecke (Human Genetics, 1999)

Genetic susceptibility to pre-eclampsia and chromosome 7q36 - G. Guo; J.A. Lade; A.N. Wilton; E.K. Moses; M. Grehan; Y. Fu; H. Qiu; D.W. Cooper; S.P. Brennecke (Human Genetics, 1999)

Expression of a conifer glutamine synthetase gene in transgenic poplar - Fernando Gallardo; Jianming Fu; Francisco R. Cantón; Angel García-Gutiérrez; Francisco M. Cánovas; Edward G. Kirby (Planta, 1999)

Inhibition of B16BL6 melanoma invasion by tyrosine and phenylalanine deprivation is associated with decreased secretion of plasminogen activators and increased plasminogen activator inhibitors - Bertha A. Pelayo; Ya-Min Fu; Gary G. Meadows (Clinical & Experimental Metastasis, 1999)

Incomplete Block Designs for Genetic Testing: Statistical Efficiencies with Missing Observations - Yong-Bi Fu; Alvin D. Yanchuk; Gene Namkoong; G. Peter Y. Clarke (Forest Science, 1999)
Missing observations are common in forest genetic field trials and are expected to reduce statistical efficiencies of any applied field designs. Such reductions could lower the presumed efficiency and other benefits of implementing any incomplete block designs (ICBs). In this study, we addressed this by computer simulation of a full-sib progeny trial with up to 20% of the observations missing. Four scenarios of missing observations (random, row, column, and genetic mortality) and tests of both clones and seedling families were examined. Two types of ICBs (alpha and no constraint) with single-tree plots, and their corresponding randomized complete block design (RCB), were considered on test sites with gradient and patchy environmental variation. Our simulations show that: (1) the statistical efficiencies of estimating family (or clone) means with both ICB and RCB were very sensitive to the percentage, not the scenarios, of missing observations examined; (2) the statistical efficiencies for both ICB and RCB were reduced as the number of missing observations increased, except in the cases of clonal genetic mortality; (3) the relative efficiency of ICB over RCB (at equal levels of missing observations) was reduced slightly as the level of missing observations increased; (4) the relative efficiencies for the seedling family tests were a little more sensitive to the levels of missing observations than those for the clonal tests, and; (5) the two ICBs showed little variation in the relative efficiencies across the missing observation scenarios and test conditions examined. Implications of these results for forest genetic field trials are discussed. For. Sci. 45(3):374-380.

Deletion of two downstream genes alters expression of the hmc operon of Desulfovibrio vulgaris subsp. vulgaris Hildenborough - Richard G. Keon; Rongdian Fu; G. Voordouw (Archives of Microbiology, 1997)

Comparative Analyses of Soil Contaminant Levels and Plant Species Diversity at Developing and Disused Oil Well Sites in Qianjiang Oilfield, China - Z.-T. Xiong; H.-X. Hu; Y.-X. Wang; G.-H. Fu; Z.-Q. Tan; G.-A. Yan (Bulletin of Environmental Contamination and Toxicology, 1997)

A one-year survey of rotavirus strains from three locations in Bangladesh - Leanne E. Unicomb; Fu Bingnan; Z. Rahim; N. N. Banu; J. G. Gomes; G. Podder; M. H. Munshi; S. R. Tzipori (Archives of Virology, 1993)